Memory as Historiography: Reading Memories of a Father by Prof. T.V Eachara Warrier (International Journal of Food and Nutritional Sciences, 2022)
The paper titled “Memory as Historiography: Reading Memories of a Father by Prof. Eachara Warrier” is an attempt to examine the intricate inter- relationship between memory and history. It seeks to analyse how the writing of memory may help formulate a narrative of history bridging the gap between the personal and the political. It undermines the distinction between the private and the public that memory and history seems to maintain. The text Memories of a Father by Prof Eachara Warrier traces the trauma of a father who lost his only son through police atrocities during a dark period in Indian History, namely the Emergency. The father’s relentless search for the missing son becomes an exposition of the historical period in which the narrative is located and formulates a subversive text that interrogates the political and ideological urtext of emergency. Thus personal memory becomes a space for unearthing the ‘other’side of the story creating an alternate historiography that challenges the narratives of the dominant discourses. Memory as historiography thus becomes the occasion for the excavation of the past, exposition of the present and an exhortation for the future.